Transitivity Shift in The Twits’ English and Its Indonesian Translated Versions - Rinda Riztya (ESENSI LINGUA, 2019)
ABSTRACT The study is aimed at finding out the equivalence of the realization of M.A.K Halliday’s transitivity in The Twits’ English and Indonesian versions, particularly to discover the similarities and the differences by the use of transitivity in both versions. Transitivity is a system which construes the world of experience into a manageable set of process types. There are six types of process in transitivity which are Material, Mental, Relational, Verbal, Behavioural, and Existential processes. Each process type has specific kinds of participant role that are systematically associated with each other. The finding shows that there are different total number of clauses between the English version (578 clauses) and the Indonesian version (561 clauses). The difference in The Twits’ English and Indonesian versions is caused by the transitivity shift which occurred in the translated version. The similarities of Transitivity in The Twits’ are Material process as the dominant process which has 270 clauses with the percentage of 46,71% in English version and 264 clauses with the percentage of 47,05% in the translated version. Furthermore, the same positions in both versions are placed by Verbal process in the third position, Existential process in the fifth position, Possessive Attributive process as the sixth position, Relational Identifying process in the seventh position, and Behavioural process in the last position. The transitivity shift in The Twits is occurred in the Indonesian version due to the fact that each language has different grammatical structures. Keywords: Transitivity, Process Types, Translation, Narrative, The Twits ABSTRAK Penelitian ini bertujuan untuk mengetahui perbandingan transitivitas The Twits dalam Bahasa Inggris dan Bahasa Indonesia, khususnya untuk mencari persamaan dan perbedaan dalam penggunaan transitivitas dalm kedua versinya. Transitivitas adalah sistem berhubungan dengan pemilihan tipe proses dan peran partisipan, yang direalisasikan ke dalam realita pengalaman. Terdapat enam tipe proses dalam transitivitas yaitu proses Material, Mental, Relational, Verbal, Behavioural, dan Existential. Tiap proses memiliki peran partisipan yang berbeda yang saling berhubungan. Temuan dari penelitian ini menunjukkan bahwa terdapat perbedaan jumlah klausa antara versi Bahasa Inggris (578 klausa) dan versi Bahasa Indonesia (561 klausa). Perbedaan antara kedua versi dalam Bahasa Inggris dan Bahasa Indonesia disebabkan oleh pergeseran transitivitas yang terjadi di dalam versi Bahasa Indonesia. Persamaan tipe proses transitivitas antara kedua versi adalah proses Material yang merupakan tipe proses yang paling dominan. Terdapat 270 klausa yang menunjukkan tipe proses Material dengan 46,71% dalam versi Bahasa Inggris dan 264 klausa dengan 47,05% dalam versi Bahasa Indonesia. Selanjutnya, di posisi kedua terdapat proses Mental, posisi ketiga dengan proses Verbal, keempat dengan proses Existential, kelima dengan proses Possessive Attributive, keenam dengan proses Relational Identifying, dan posisi terakhir dengan proses Behavioural. Pergeseran transitivitas dalam buku The Twits terjadi pada versi Bahasa Indonesia dikarenakan kedua bahasa memiliki perbedaan struktur gramatikal.